Social observation modulates the influence of socioeconomic status on pro-environmental behavior: an event-related potential study - Zhong, Bowei; Niu, Nana; Li, Jin; Wu, Yun; Fan, Wei (Frontiers in Neuroscience, 2024)
Understanding the psychological antecedents of socioeconomic status (SES) on proenvironmental behavior is crucial for effectively encouraging individuals from different socioeconomic backgrounds to address environmental issues. Previous research has separately examined the influence of SES and social observation on pro-environmental behavior. However, little is known about whether social observation moderates the influence of SES on pro-environmental behavior, and the underlying neurophysiological mechanisms remain uncharacterized. Using event-related potential (ERPs), we adopted the green purchase paradigm and manipulated subjective SES, to examine whether the influence of SES on pro-environmental behavior is moderated by social observation. The behavioral results revealed that individuals of high SES tended to purchase more eco-friendly products under the observable condition than those in the non-observable condition. The ERP results revealed that participants with high SES exhibited more negative N2 and N400 amplitude during environmental decisions in the non-observable condition than in the observable condition, indicating that high SES individuals experience less cognitive conflict during environmental decisions, which may reflect the attenuated cost-benefit calculation due to reputational incentives in the presence of observers.Additionally, individuals with high SES exhibited greater reputational motivation when observed, as indicated by larger P3 amplitude. However, these differences were not observed among individuals with low SES. These findings suggest that SES is associated with distinct psychological and behavioral differences in pro-environmental behavior, moderated by social observation, evident across both the early and later stages of environmental decisions in the brain.